ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA PT. MARUKI INTERNASIONAL INDONESIA - Andi Mulia Saleh (AkMen JURNAL ILMIAH, 2020)
The purpose of this study was to determine the control of raw material inventory at PT. Maruki Internasional Indonesia uses the EOQ (Economic Order Quantity) method to minimize inventory costs. The type of data used is quantitative data and qualitative data. The data sources used are primary data and secondary data. The analysis method used is quantitative descriptive using the Economic Order Quantity (EOQ) method. The results showed that the control of raw material inventory at PT. Maruki Internasional Indonesia, if you use the EOQ (Economic Order Quantity) method, can minimize inventory costs